2021
DOI: 10.3390/ani11082256
|View full text |Cite
|
Sign up to set email alerts
|

Dead-End (dnd) Gene Cloning and Gonad-Specific Expression Pattern in Starry Flounder (Platichthys stellatus)

Abstract: dnd is a germline-specific maternal RNA expressed in various vertebrate classes, which encodes an RNA-binding protein that is essential for PGC migration. The purpose of this study is fundamental research about starry flounder dnd gene for germ cell marker development. In this study, we cloned and analyzed the expression levels of Platichthys stellatus dead end (psdnd) in various tissues and embryonic stages. The psdnd gene was isolated from starry flounder ovaries, cloned into a pGEM-t vector, and sequenced. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…Ontogenetic variations in the level of ddx4 mRNA in several fish species have demonstrated that maternal transcripts of ddx4 persist, and their amounts have been shown to be relatively high at the early developmental stage and diluted in later embryogenesis [ 18 , 20 , 51 , 52 ]. A similar ontogenetic expression pattern of dnd during embryo development has also been revealed in a number of fish [ 9 , 11 , 15 , 19 , 21 , 29 , 65 , 66 ]. The present study determined the expression levels of ddx4 and dnd1 , which have different patterns, from hatching through to early larval development at 35 dph (1 cm).…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…Ontogenetic variations in the level of ddx4 mRNA in several fish species have demonstrated that maternal transcripts of ddx4 persist, and their amounts have been shown to be relatively high at the early developmental stage and diluted in later embryogenesis [ 18 , 20 , 51 , 52 ]. A similar ontogenetic expression pattern of dnd during embryo development has also been revealed in a number of fish [ 9 , 11 , 15 , 19 , 21 , 29 , 65 , 66 ]. The present study determined the expression levels of ddx4 and dnd1 , which have different patterns, from hatching through to early larval development at 35 dph (1 cm).…”
Section: Discussionsupporting
confidence: 57%
“…Similar specific expressions of ddx4 mRNA in the gonads have been demonstrated in rainbow trout [ 50 ], medaka [ 51 ], tilapia [ 30 ], gibel carp [ 52 ], rice field eel [ 53 ], Pacific bluefin tuna [ 54 ], carp [ 55 ], catfish [ 18 ], European seabass [ 56 ], rare minnow [ 57 ], Atlantic cod [ 58 ], Korean rockfish [ 59 ], Solea senegalensis [ 60 ], toadfish [ 61 ], Japanese flounder [ 20 ], brown-marbled grouper [ 31 ], striped catfish [ 7 ], and Mekong giant catfish [ 62 ]. Coincidentally, the specific expression of dnd1 in testes and ovaries was revealed in zebrafish [ 15 ], medaka [ 29 ], rare minnow [ 63 ], gibel carp [ 13 ], tambaqui [ 64 ], Atlantic salmon [ 65 ], and starry flounder [ 21 ]. In addition, in situ hybridization using antisense ddx4 and dnd1 probes demonstrated that ddx4 and dnd1 mRNAs were observed in germ cells at various stages, and strong expression was observed in immature germ cells in testes, including spermatogonia, PSC, and SSC, and in ovarian cells such as oogonia and primary oocytes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In mice, dnd is only detectable in testis [ 5 ], whereas it is restricted to the ovary in frog [ 6 ]. Dnd occurs in germ cells of both sexes in medaka [ 8 ], zebrafish ( Danio rerio ) [ 4 ], carp ( Carassius gibelio ) [ 10 ], turbot ( Scophthalmus maximus ) [ 13 ] and starry flounder ( Platichthys stellatus ) [ 14 ].…”
Section: Introductionmentioning
confidence: 99%